Given :-
... ( 2x + 3y - 4z ) - ( x - y - z )
... 2x + 3y - 4z - x + y + z
... x + 4y - 3z is the answer.
Hope it helps!
Answer:
Step-by-step explanation:
The Fundamental Theorem of Algebra states that the number of complex roots a polyomial has is equal to its highest exponent. This is a squared polynomial; second degree; quadratic. When it is factored, no matter what types of numbers you get as the solution, you will ALWAYS have 2 of them. When this quadratic is factored, we get that x = 3 and x = 3. That means that this is a quadratic that touches the x-axis at (3, 0). It doesn't go through, it only touches. We do have 2 roots, but since they're the same, we say we have a multiplicity 2 of that root. The closest you'll come to that in your choices is A. Apparently your text refers to multiplicity 2 as a double root.
Answer:
x^3/2 - 6x^1/2
Step-by-step explanation:
f(x) = x - 6
g(x) = x^1/2
g(x) * f(x) = x^1/2(x - 6)
g(x) * f(x) = x^3/2 - 6x^1/2
1/3 because there are 3 people and only one correct answer
A): 2013 = 149.32
Find difference of: 194.31
2014 = 194<u>.31</u> <u>149.32</u>
= <u>44.99</u>
<u>2015</u> Total Will Be:
B):
149.32 + 25 = 174.32
(2013)
<h3> 174.32 + 44.99 = 219.31</h3>
(B) (A)